Integrating electrochemical pre-treatment with carrier-based membrane bioreactor for efficient treatment of municipal waste transfer stations leachate. (July 2023) - Song, Zi; Sun, Feiyun; Xing, Dingyu; Liao, Runfeng; Zhang, Xinbo; Wang, Mingming; Su, Xiaoli; Wen, Zheng; Dong, Wenyi
Graphical abstract: Highlights: An integrated process was constructed for fresh leachate from waste transfer stations. Leachate was stably treated to satisfy Chinese discharge standard within an HRT of 40 h. Physicochemical pre-treatment effectively removed large amounts of refractory organics. Biotreatments realized SND and achieved efficient organic and nitrogen removal. Carriers in the oxic MB-MBR accumulated attached biomass and alleviated fouling. Abstract: An integrated process of electrochemical pre-treatment with carrier-based membrane bioreactor (MBR) was constructed for fresh leachate from waste transfer stations with high organic and NH4 + -N content. Results showed that within a hydraulic retention time 40 h, the removal efficiencies of chemical oxygen demand (COD), NH4 + -N, suspended solids (SS) and total phosphorus (TP) were over 98.5%, 91.2%, 98.3% and 98.4%, respectively, with the organic removal rate of 18.7 kg/m 3 . The effluent met the Grade A Standard of China (GB/T31962-2015). Pre-treatment contributed about 70 % of the degraded refractory organics and almost all the SS, with the transformation of the humic-like acid to readily biodegradable organics. Biotreatment further removed over 50% of nitrogen pollutants through simultaneous nitrification and denitrification (SND) and consumed about 30% of organics. Meanwhile, the addition of carriers in the oxic MBR enhanced the attached biomass and denitrification enzyme activity, alleviating membrane fouling.